HOUSE PRICE CHANGES AND ISLAMIC BANK STABILITY: EVIDENCE FROM MALAYSIA - Shiau Hui Kok; Normaz Wana Ismail (Journal of Islamic Monetary Economics and Finance, 2019)
In this paper, we examine the relationship between house price and Islamic bank stability in Malaysia. In particular, in relating to Islamic bank stability to Malaysian house price changes, we evaluate the nature of the relationship from the perspective of nonlinearities. The Autoregressive Distributed Lag (ARDL) model is applied to a sample that consists of 9 Islamic banks in Malaysia for the period of 2000-2016. Our results indicate that there is an inverted U-shaped relationship between house price and Islamic bank stability in the long run. Meanwhile, the relationship is insignificant in the short-run. To put it differently, initially, the higher house prices, the more stable the bank. Then, the impact of house prices on bank stability becomes negative when house prices surpass the threshold point. As far as the bank-specific characteristics are concerned, the cost to income ratio is found to significantly and negatively related to the bank stability. Such a result has policy implications in which it is crucial for achieving balance in the housing market, and efficiently managing the cost is equally important to ensure Islamic bank soundness.